2020
DOI: 10.1097/bpb.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for failure of temporary hemiepiphysiodesis in Blount disease: a systematic review

Abstract: There is limited information regarding the use of temporary hemiepiphysiodesis for Blount disease. We performed a systematic review of patients treated for Blount disease using either extraperiosteal staples or plates to identify characteristics affecting clinical outcome, including the need for unplanned procedures. A total of 53 patients (63 bone segments) underwent temporary hemiepiphysiodesis at a mean age of 8.8 years (1.8-14.7 years). Overall, 32/63 (51%) segments achieved neutral mechanical axis and 31/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 29 publications
4
27
1
Order By: Relevance
“…Complete correction of the mTFA, MAD, and MAZone by GMS, was only successful in 40%, 47%, and 49% of limbs, respectively. The definition of success for hemiepiphyseodesis and GMS in LOTV has no clear consensus among investigators 6–10,15–17. Reported success rates of achieving normal adult limb parameters range from 33% to 67%, comparable to our study 7,10,15,16.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Complete correction of the mTFA, MAD, and MAZone by GMS, was only successful in 40%, 47%, and 49% of limbs, respectively. The definition of success for hemiepiphyseodesis and GMS in LOTV has no clear consensus among investigators 6–10,15–17. Reported success rates of achieving normal adult limb parameters range from 33% to 67%, comparable to our study 7,10,15,16.…”
Section: Discussionsupporting
confidence: 74%
“…The reported success of hemiepiphyseodesis for the management of tibia vara through “growth modulation” has been disappointing when compared with other diagnoses 4–6. The literature cites age, severity of deformity, and body mass index (BMI) as predictors of poor results of hemiepiphyseodesis in LOTV 6–10. However, these conclusions are predicated on studies, which frequently have small sample sizes, heterogeneous groups of patients (early and late-onset) managed with varying techniques, or results from meta-analyses 6,9.…”
mentioning
confidence: 99%
“…The explanation we could use is that children reach skeletal maturity before total correction. Recently a systematic review by Fan et al found no correlation between age at surgery or implant type and hemiphysiodesis failure, but their database was heterogeneous [16]. Another complication related to growth rebound with recurrence of the deformity suggests waiting for valgus hypercorrection before removing the material.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Implant failure is more common in patients with obesity and the population under the age of 10 years, and it is recommended to use larger or more solid screws with stronger constructs. [28] Different sizes of K-wire and cerclage are used frequently in the clinical practice. We believe that a larger K-wire and cerclage can be used to increase the fixation strength.…”
Section: Discussionmentioning
confidence: 99%